2020
DOI: 10.4103/aca.aca_203_18
|View full text |Cite
|
Sign up to set email alerts
|

High thoracic epidural decreases perioperative myocardial ischemia and improves left ventricle function in aortic valve replacement alone or in addition to cabg surgery even with increased left ventricle mass index

Abstract: Introduction: High thoracic epidural (HTE) may reduce perioperative tachyarrhythmias, respiratory complications and myocardial ischemia (MI) and it may increase coronary perfusion and myocardial oxygen balance through sympatholysis and pain control. The aim of this study is to investigate the benefit of HTE in patients undergoing aortic valve replacement (AVR) alone or in addition to coronary artery bypass graft (CABG). Methods: This prospective randomized controlled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…22 However, the use of TEA decreased the incidence of myocardial infarction (MI), and it enhanced left ventricle (LV) function in patients undergoing aortic valve replacement alone or in combination with CABG, even when the left ventricular mass was increased. 23 …”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…22 However, the use of TEA decreased the incidence of myocardial infarction (MI), and it enhanced left ventricle (LV) function in patients undergoing aortic valve replacement alone or in combination with CABG, even when the left ventricular mass was increased. 23 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Cardiac surgery requires anticoagulants, and it is not widely accepted due to concerns about neuraxial hematoma following anticoagulants. 1 , 14 , 21 , 22 , 23 , 24 , 25 , 26 A few trials have demonstrated the safety of regional anesthetic and analgesic techniques in the context of possible anticoagulation during cardiac surgery. 1 , 19 Regional blocks have enormous potential to be integrated into hospitals' acute pain management paradigms following cardiac surgery, given their initial success in decreasing pain scores and reducing opiate usage.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[15,16] TEA has been reported to improve ventricular function, minimize the risk of myocardial infarction, and reduce the development of rhythm disorders. [17,18] The positive effects of TEA on postoperative morbidity and mortality have been reported in several studies in the literature. However, the number of studies investigating the effects of TEA on the geriatric patient population undergoing open heart surgery is few.…”
Section: Introductionmentioning
confidence: 95%